2018
DOI: 10.3892/or.2018.6786
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic acid suppresses the invasion of HepG2 cells via downregulation of HGF/c‑Met signaling

Abstract: Liver cancer is one of the most devastating types of cancer worldwide. Despite years of improvements in treatment, the prognosis of patients with this type of malignancy remains poor due to frequent recurrence and metastasis after surgical resection. Ginkgolic acid (GA) is a botanical drug extracted from the seed coat of Ginkgo biloba L. that possesses a wide range of bioactive properties. However, to the best of our knowledge, whether GA can inhibit the invasion of liver cancer cells and the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Collectively, the results of the present study indicated that GA suppressed the development of RCC. These results were consistent with previous studies demonstrating that GA plays an inhibitory biological role in cancer (12)(13)(14)(15)25). However, the biological effect of GA on RCC was observed at high concentrations of GA in vitro and it is uncertain whether this concentration would be possible in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Collectively, the results of the present study indicated that GA suppressed the development of RCC. These results were consistent with previous studies demonstrating that GA plays an inhibitory biological role in cancer (12)(13)(14)(15)25). However, the biological effect of GA on RCC was observed at high concentrations of GA in vitro and it is uncertain whether this concentration would be possible in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Extracts from natural plants are becoming an increasingly popular strategy to identify novel antitumor compounds (23,24). Recently, several studies have reported that GA displays promising antitumor activities (12)(13)(14)(15). Therefore, identification of the regulatory mechanism of GA in tumorigenesis would provide valuable insight for the treatment of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations